GENDER ANALYSIS OF URBAN VEGETABLE PRODUCTION IN OJO LOCAL GOVERNMENT AREA, LAGOS STATE, NIGERIA - FAPOJUWO , O.E.; AYODEJI, A. O.; OKUBENA , B.A.; AJAYI, M.T.; IDRIS , O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
Urban vegetable production has been discovered to be a viable poverty intervention strategy for the urban poor, and in-depth understanding of the gender perspective to its production is imperative. The study assessed gender analysis of urban vegetable production in Ojo Local Government Area, Lagos State, Nigeria. A snowball sampling procedure was used to select 106 respondents for the study and primary data were collected with the aid of a questionnaire. The average age of the respondents was 45 years, the majority (59.4%) of them were female, 72.6% were married, 48.1% had secondary education, 50.0% hired labour with average farmland of 2 hectares, and farming experience and family size were11 years and five people respectively. Males participated more in harvesting for sale (𝑥̅=3.79) and irrigation (𝑥̅=3.09), while females participated more in marketing (𝑥̅=3.76), purchasing seeds/seedlings (𝑥̅=3.46), and spraying (𝑥̅=3.44). The major reasons responsible for male and female participation in urban vegetable production were a passion for vegetable farming (𝑥̅=4.33) and improved household nutrition (𝑥̅=4.27). Respondents were mostly constrained by high costs of inputs (𝑥̅=2.72), pests and diseases (𝑥̅=2.59), and poor funding (𝑥̅=2.56). Significant (p<0.05) relationships existed between source of farm labour (χ2= 18.38, df=3), farming experience (r=0.22), family size (r=-0.26), andconstraints facing respondents’ production(r=0.28) with participation in urban vegetable production. Significant differences exist between male and female participation in vegetable production (t=1.05, p<0.01). Therefore, providing more financial assistance, seeds and an enabling environment will further enhance male and female participation in urban vegetable production.